Psychometric Test of the Routine Exercise Intention Measurement Tool - Sahlah Nafiah; Aisyah Maulidah Hasanah; Muhamad Farhan; Syofiatun Priandini; Asma Fauziyyah Ulya; Titi Sahidah Fitriana (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
The aim of this study was to develop and evaluate a measurement tool for regular exercise intention based on the Theory of Planned Behavior, focusing on its validity and reliability. The instrument consisted of four core dimensions: intention, perceived behavioral control (PBC), attitude, and subjective norm. The development process included setting objectives, identifying constructs, exploring salient beliefs through interviews, compiling items, conducting qualitative selection, and performing psychometric testing. The initial version applied a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree), and only items with correlation coefficients above 0.2 were retained. Construct validity was examined through correlations with EQ-5D-5L scores and a contrast group analysis comparing students who exercised regularly with those who did not. Reliability was assessed using Cronbach’s Alpha. A total of 69 active students aged 18–25 years participated in the study. The results showed that all four dimensions had significant correlations with both the LSS and VAS EQ-5D-5L scores. Group contrast analysis demonstrated that the instrument could distinguish between intention and PBC, but not between attitude and subjective norms. Reliability values ranged from 0.794 to 0.888, indicating strong internal consistency. Overall, the instrument proved to be valid and reliable; however, testing with larger and more diverse samples is recommended to enhance generalizability and discriminant validity.